Controllable formation of unusual homocrystals in poly(l‐lactic acid)/poly(d‐lactic acid) asymmetric blends induced by the constraining effects of pre‐existing stereocomplexes. Issue 5 (8th September 2020) - Xie, Qing; Xu, Wenqing; Zhou, Jian; Zheng, Ying; Shan, Guorong; Bao, Yongzhong; Pan, Pengju
Abstract : Synchrotron radiation wide‐angle X‐ray diffraction and small‐angle X‐ray scattering techniques have been used to investigate and elucidate the formation conditions, mechanism and phase transition of an unusual homocrystalline polymorph in stereocomplexable polymers. Abstract : Crystallization in confined environments usually induces polymers showing complicated crystallization kinetics and unusual crystalline structure. Beyond the typical confined polymer systems, pre‐existing crystals can also exert confinement effects on the subsequent crystallization of polymorphic or multi‐component polymers; this, however, is not well understood at present. Herein, poly(l ‐lactic acid)/poly(d ‐lactic acid) (PLLA/PDLA, abbreviated as L/D) asymmetric blends with various PDLA fractions ( f D = 0.02–0.5) are chosen as a model system and the effects of pre‐existing stereocomplexes (SCs) on the crystallization kinetics and polymorphic structure are investigated. It is found that unusual β‐form homocrystals (HCs) of poly(lactic acid) can be formed in an asymmetric L/D blend, which are strongly influenced by the molecular weights (MWs) of the used polymers, L/D mixing ratio, thermal treatment temperature ( T max ) and crystallization temperature ( T c ). The formation of β‐HCs is preferred in asymmetric L/D blends with low and medium MWs, medium f D (0.1–0.2), medium T max (170–200°C), and low T c (70–110°C). The metastable β‐HCs reorganize into the more stable α‐HCs via melt recrystallization in the heating process. It is proposed that the β‐HC formation stems from the constraining effects of pre‐existing SCs; this constraining effect is governed by the content of pre‐existing unmelted SCs in the thermally treated samples.